A Novel Session Payment System Via Internet Of Things (IOT) - Ali, Mohanad Faeq; Abu, Nor Azman; Harum, Norharyati (Research India Publications, 2017)
A wireless method has been designed to process a financial payment efficiently. A user can just swipe his/her credit/debit card over the counter and all the processing needed shall be done seamlessly. A smartphone is a popular device to carry around. It is a hassle to carry and keep track on so many debit/credit cards in a wallet. It is more convenient to carry a debit/credit card electronically on a smartphone. This paper will embark on an electronic debit/credit card on a smartphone and migrate to IoT money. A novel session payment system using IoT money shall be introduced to minimise debit/credit card risk. The scope of this paper is confined into the security model for an easy payment system based on Internet of Things (IoT). Since each IoT money is unique to each payment, this session payment system will ease the burden on protecting the database of the payment system.